Chemistry and bioactivity of nobiletin and its metabolites - Shiming Li; Hong Wang; Limin Guo; Hui Zhao; Chi-Tang Ho (Journal of Functional Foods, 2014)
The studies of nobiletin and other polymethoxyflavones from citrus peels become prevalent in recent years due to many well-established evidences showing their multiple efficacious biological activities. The biotransformation study of polymethoxyflavones, particularly nobiletin has emerged along with the significant findings of nobiletin bioactivity. Major nobiletin metabolites from rodent biofluids have been successfully characterized, isolated or synthesized for the evaluation of their biological activities and subsequently revealed that nobiletin metabolites demonstrate similar efficacies or more potent anti-oxidant activity and scavenging property against free radicals and in the inhibition of inflammation and cancer growth, and the prevention of metabolic syndrome and cardiovascular diseases. This review starts with basic chemistry of nobiletin and other polymethoxyflavones, highlights their biological properties and recent findings and summarizes nobiletin’s biotransformation and biological activities of the main nobiletin metabolites.